PEMBINAAN GENERASI MUDA PEDULI LINGKUNGAN MELALUI GERAKAN LAUDATO SI’ INDONESIA - Saptadi, Norbertus Tri Suswanto; Grace Theresia Pontoh (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2025)
Developing a young generation who cares about the environment is both a challenge and a necessity in the modern era. The Indonesian Laudato Si' movement is present as a concrete form of internalizing integral ecological values as stated in the encyclical Laudato Si' by Pope Francis. PkM aims to form a young generation of churches who have environmental awareness, provide a theological understanding of human responsibility towards the natural world, train the young generation to take an active role in environmental conservation, and instill Christian values in protecting and caring for the environment. The PkM method consists of preparation and coordination, socializing the Laudato Si' Movement, building ecological awareness, practicing waste management, cleaning the surrounding environment, and distributing questionnaires. Community service activities in an effort to develop young people who care about the environment through assessment through questionnaire results in the form of